1998
DOI: 10.1016/s0014-5793(98)00552-3
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the `35‐μs kinetics' of P680+⋅ reduction in photosystem II with an intact water oxidising complex

Abstract: The origin of the`35-W Ws kinetics' of P680 c reduction in photosystem II (PS II) with an intact water oxidising complex has been analysed by comparative measurements of laser flash induced changes of the 830-nm absorption and the relative quantum yield of chlorophyll (Chl) fluorescence. The latter parameter was monitored at a time resolution of 500 ns by using newly developed home built equipment [Reifarth, F., Christen, G. and Renger, G. (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 31 publications
11
46
0
1
Order By: Relevance
“…Recent studies with isolated LHC II revealed that in the time domain of 1-100 µs the fluorescence yield only depends on formation of 3 Car and its decay with a characteristic 3 µs kinetics under aerobic conditions (27,48,49). Accordingly, after correction for these 3 µs kinetics, the fluorescence rise reflects the kinetics of P680 +• reduction by Y Z whereas the P680 +• Q A -• recombination is "invisible".…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies with isolated LHC II revealed that in the time domain of 1-100 µs the fluorescence yield only depends on formation of 3 Car and its decay with a characteristic 3 µs kinetics under aerobic conditions (27,48,49). Accordingly, after correction for these 3 µs kinetics, the fluorescence rise reflects the kinetics of P680 +• reduction by Y Z whereas the P680 +• Q A -• recombination is "invisible".…”
Section: Methodsmentioning
confidence: 99%
“…At about 45 µs after the actinic flash, a maximum level symbolized by F m -(45 µs) is reached. At saturating intensity of the actinic laser flash, the ratio of F m (45 µs)/F 0 is about 2.7, which is typical for the flash-induced increase of the relative fluorescence quantum yield (14,28). It is slightly lower (by about 20%) than values reported recently for the F m /F 0 ratio of 3.2 measured at a delay of 100 µs (14,28) because at 45 µs the slow rise components with lifetimes of the order of 30 µs are not completed.…”
Section: Flash-induced Fluorescence Changes In Thylakoidsmentioning
confidence: 97%
“…The extent of a 3 is gathered from the difference ∆Φ( 3 Car) shown in Figure 3. The contribution of the 35 µs kinetics of P680 •+ reduction by Y Z due to relaxation processes (11,14,16,28) is comparatively small and can be neglected in the time domain of e5 µs.…”
Section: Changes Of Relative Fluorescence Yield In Dark-adapted Thylamentioning
confidence: 99%
“…On the contrary, DF has components that decay in very different time domains: in the nanoseconds (Christen et al 2000), microseconds (Jursinic and Govindjee 1977;Jursinic et al 1978;Wong et al 1978;Christen et al 1998;Mimuro et al 2007;Buchta et al 2008), milliseconds (Hipkins and Barber 1974;Barber and Neumann 1974;Zaharieva and Goltsev 2003;Goltsev et al 2005;Buchta et al 2007), seconds Hideg et al 1991;Katsumata et al 2008), and even in the hour time range (Hideg et al 1990).…”
Section: Origin Of Delayed Fluorescencementioning
confidence: 99%